Assessment of the efficacy of a feed additive consisting of Bifidobacterium longum CNCM I‐5642 (PP102I) for dogs (Nestlé Enterprises S.A.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the efficacy of Bifidobacterium longum CNCM I‐5642 (PP102I) as a zootechnical feed additive (functional group: physiological condition stabiliser) for dogs. In a previous opinion, the FEEDAP Panel concluded that PP102I was safe for dogs and the environment. Regarding the safety for the users, the Panel concluded that the additive should be considered a skin and respiratory sensitiser. Due to the lack of data, no conclusions could be drawn on the potential for skin/eye irritancy of the additive. Due to the lack of sufficient data, the Panel could not conclude on the efficacy of the additive for dogs at the proposed conditions of use. The applicant submitted in vitro eye and skin irritation tests and one efficacy trial in dogs to address the inconclusive aspects of the previous assessment. Based on the data provided, the Panel considers that the additive is irritant to the eyes but not to the skin. The additive has the potential to be efficacious when included in feed for dogs at 1 × 109 colony forming unit (CFU)/dog per day (which would correspond approximately to 3.5 × 109 CFU/kg complete feed).